New Black Feminist Criticism, 1985-2000 - Christian, Barbara, 1943-2000 (Book collections on Project MUSE., 2007)
A passionate and celebrated pioneer in her own words New Black Feminist Criticism, 1985-2000 collects a selection of essays and reviews from Barbara Christian, one of the founding voices in black feminist literary criticism. Published between the release of her second landmark book Black Feminist Criticism and her death, these writings include eloquent reviews, evaluations of black feminist criticism as a discipline, reflections on black feminism in the academy, and essays on Toni Morrison, Alice Walker, Paule Marshall, and others.